2021
DOI: 10.1007/s00234-021-02783-y
|View full text |Cite|
|
Sign up to set email alerts
|

Gray matter volume reduction with different disease duration in trigeminal neuralgia

Abstract: Purpose Structural magnetic resonance imaging is widely used to explore brain gray and white matter structure in trigeminal neuralgia (TN) but has yielded conflicting findings. This study investigated the relationship between disease duration as a clinical feature of TN and changes in brain structure. Methods We divided 49 TN patients into three groups (TN1–TN3) based on disease duration (TN1 = 1.1 ± 0.7 (0–2) years, TN2 = 4.8 ± 1.5 (3–7) years, TN3 = 15.1 ± 5.5 (10–30)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 56 publications
2
7
0
Order By: Relevance
“…The involvement of brain motor areas observed in patients suffering chronic pain may stem from the fact that they are often forced to restrict their movements and learn to act differently in order not to provoke or exacerbate pain. Consistent with this trend, studies focusing on patients with trigeminal neuralgia have also reported noticeable structural changes occurring in motor-related areas of these individuals [12,36].…”
Section: Discussionsupporting
confidence: 56%
“…The involvement of brain motor areas observed in patients suffering chronic pain may stem from the fact that they are often forced to restrict their movements and learn to act differently in order not to provoke or exacerbate pain. Consistent with this trend, studies focusing on patients with trigeminal neuralgia have also reported noticeable structural changes occurring in motor-related areas of these individuals [12,36].…”
Section: Discussionsupporting
confidence: 56%
“…The local amyloid deposition in the locus coeruleus and the norepinephrine derangement could explain the initial mild cognitive impairment and the early AD symptoms due to hippocampal diencephalic and para-hippocampal retro splenial network involvement [ 94 ]. A similar process could involve the entorhinal cortex as many studies on trigeminal neuralgia are showing an overall gray matter volume reduction in patients with chronic diseases [ 95 ]. The increasing burden of P. gingivalis and the inflammation and leakage of inflammatory mediators from the established periodontal disease lesions may initiate the latter effects of gingipains in the alteration of BBB permeability [ 53 ].…”
Section: Could the Trigeminal Nerve Pathway Act As The Entrance For ...mentioning
confidence: 96%
“…However, we did not observe GMV alterations in basal ganglia and thalamus in patients with CTN, which were caused by the different disease durations of CTN in our study. This is supported by Shen et al’s (2022) study, which used VBM to investigate the changes in brain structure in patients with CTN grouped according to disease duration and they found GMV alterations in different brain regions at different stages of CTN. Tsai et al (2018) found reduced volume in the thalamus, but along with the duration of the disease, the volume of the thalamus gradually increased.…”
Section: Discussionmentioning
confidence: 71%